Comparative Analysis of Talent Management Implementation in Agam, Indonesia, and Local Governments in South Korea and Russia - Dwiputrianti, Septiana; Kotchegura, Alexander; Lee, Hye Kyoung; Wahyuni, Sri (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2025)
This study examines an integrated model of talent management in the context of Agam's local government. To provide specific recommendations, this research analyses Agam's talent management systems, considering best practices from South Korea and Russia and seeks to identify gaps. A qualitative case study design was employed, and semi-structured interviews were held with selected participants, which led to the creation of an ITM model that accounts for Agam's specific socio-political and economic context. The study's findings suggest that the talent management systems in Agam face TM access restrictions due to limited training opportunities, insufficient skill evaluation, and retention issues of skilled personnel during political transitions. In contrast, Russia and South Korea adopt more sophisticated talent management (TM) approaches, including systematic talent assessment, performance-based promotion, and extensive training, to improve workforce competency. This ITM model defines talent management within the framework of competency-based management and inclusivity, providing practical approaches towards the challenges of talent attraction, development, and retention. Drawing on insights from South Korean and Russian practices, this study provides a basis for developing a strategy to improve TM in Agam. The study emphasises the significance of tailored TM strategies while providing recommendations for policymakers aimed at improving governance and the performance of public administration in developing areas.